2013
DOI: 10.14254/2071-8330.2013/6-2/2
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Advertising Attractiveness on the Purchase Decisions of Women and Men

Abstract: is article attempts to document diff erences in purchase decisions of men and women. Earlier research has found that they, due to their diff erent upbringing and socialization along with various other social, biological and psychological factors, depict diff erent types of consumer behaviour. e purpose of this study is to investigate the infl uence of advertising attractiveness on male and female purchase decisions. e aim of the paper is to present the authorial research procedure which proposes the usage of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…It is characteristic that women are interested in higher standard dwellings and at the same time they are aware of and prepared for all the additional costs this entails. Consequently, today's marketing activities are specifically oriented towards the fairer sex, since-in the opinion of real estate agents and professionals in the field-women usually have the final word when it comes to buying a home [73,74].…”
Section: Characteristics Of the Study Sample: Age Gendermentioning
confidence: 99%
“…It is characteristic that women are interested in higher standard dwellings and at the same time they are aware of and prepared for all the additional costs this entails. Consequently, today's marketing activities are specifically oriented towards the fairer sex, since-in the opinion of real estate agents and professionals in the field-women usually have the final word when it comes to buying a home [73,74].…”
Section: Characteristics Of the Study Sample: Age Gendermentioning
confidence: 99%
“…For example, several preliminary studies have shown that there is a positive relationship between advertising attractiveness (Amandeep et al. , 2017; Furaji et al. , 2013), influencer marketing (Kavaliauskienė & Margis, 2017; Lou & Yuan, 2019) and online customer review (Guo et al.…”
Section: Discussionmentioning
confidence: 99%
“…This study's result has interesting implications for researchers and managers. Apart from many previous studies that examine the relationship between advertising attractiveness (Furaji et al. , 2013; Khuong, 2015; Triyono et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations